Chronic Kidney Disease and Nephrology Care in People Living with HIV in Central/Eastern Europe and Neighbouring Countries-Cross-Sectional Analysis from the ECEE Network - Matłosz, Bartłomiej; Skrzat-Klapaczyńska, Agata; Antoniak, Sergii; Balayan, Tatevik; Begovac, Josip; Dragovic, Gordana; Gusev, Denis; Jevtovic, Djordje; Jilich, David; Aimla, Kerstin; Lakatos, Botond; Matulionyte, Raimonda; et al. (International journal of environmental research and public health, 2022)
Chronic kidney disease (CKD) is a significant cause of morbidity and mortality among patients infected with human immunodeficiency virus (HIV). The Central and East Europe (CEE) region consists of countries with highly diversified HIV epidemics, health care systems and socioeconomic status. The aim of the present study was to describe variations in CKD burden and care between countries. The Euroguidelines in the CEE Network Group includes 19 countries and was initiated to improve the standard of care for HIV infection in the region. Information on kidney care in HIV-positive patients was collected through online surveys sent to all members of the Network Group. Almost all centres use regular screening for CKD in all HIV (+) patients. Basic diagnostic tests for kidney function are available in the majority of centres. The most commonly used method for eGFR calculation is the Cockcroft-Gault equation. Nephrology consultation is available in all centres. The median frequency of CKD was 5% and the main cause was comorbidity. Haemodialysis was the only modality of treatment for kidney failure available in all ECEE countries. Only 39% of centres declared that all treatment options are available for HIV+ patients. The most commonly indicated barrier in kidney care was patients' noncompliance. In the CEE region, people living with HIV have full access to screening for kidney disease but there are important limitations in treatment. The choice of dialysis modality and access to kidney transplantation are limited. The main burden of kidney disease is unrelated to HIV infection. Patient care can be significantly improved by addressing noncompliance.
Keywords: HIV Infections; HIV infekce; Renal Insufficiency, Chronic; lidé; Europe; Nephrology; nefrologie; Evropa; Cross-Sectional Studies; východní Evropa; Europe, Eastern; průřezové studie; chronická renální insuficience; Humans